Using circular RNAs to target toxic RNA-binding proteins in amyotrophic lateral sclerosis - Anne Kruse Hollensen; Matilde Helbo Sørensen; Sofie Vesterbæk Thomsen; Henriette Sylvain Thomsen; Christian Kroun Damgaard (Molecular Therapy: Methods & Clinical Development, 2025)
Amyotrophic lateral sclerosis (ALS) is characterized by motor neuron degeneration and is in many cases associated with mutations in genes encoding RNA-binding proteins (RBPs), including fused in sarcoma (FUS) and heterogeneous nuclear ribonuclearprotein A1 (hnRNPA1). These mutations often cause cytoplasmic mislocalization and aggregation of these typically nuclear proteins. Current treatment options for ALS are limited, highlighting the need for new therapeutic strategies. Here, we demonstrate an approach using circular RNAs (circRNAs) to target disease-associated RBPs for degradation. We designed circRNAs containing binding sites for both the target RBPs (FUS or hnRNPA1) and ring finger and CCCH-type domains 2 (RC3H2), an RNA-binding E3 ubiquitin ligase. Through RNA immunoprecipitations and protein analyses, we show that these circRNAs can form ternary complexes with their target RBPs and RC3H2. Importantly, we observed significant reductions in steady-state protein levels of ALS-associated FUS-P525L (20%) and hnRNPA1-P288S (30%) mutants when treated with their respective targeting circRNAs. These findings provide proof of concept for using circRNAs as scaffolds to promote the degradation of disease-associated RBPs, establishing a foundation for developing advanced RNA-based therapeutic strategies for ALS and potentially other RBP-related diseases.